Ecological Study of the Great Indian Bustard - Bhatia, H. M. (Indian Forester, 1986)
The Great Indian Bustard is a bird of open areas with shrubby vegetation. In view of increasing developmental activities it is now confined to the western part of the "Thar Desert" in Rajsthan, where it is sustaning a large number and multiplying too. It is a magnificent large bird and it facing extinction due to certain misbelief and poaching incidents. It is omnivorous in feeding habits. The Great Indian Bustard lays a single egg that too in the open, which is a hindrance in its multiplication. It has a peculiar courtship displaying, inflating a pouch from its neck. More than 200 birds are estimated in Jaisalmer area. It is also breeding there if sanctuaries sad national parks are created where G.I.B. is confined, then this bird can be saved from extinction.